A new taekwondo-specific field test for estimating aerobic power, anaerobic fitness, and agility performance - Taati, B.; Arazi, H.; Bridge, C. A.; Franchini , E. (PLOS ONE, 2022)
The present study aimed to propose a new multidimensional taekwondo-specific test to estimate aerobic power, anaerobic fitness, and agility. Out of sixty-five male volunteers, forty-six, forty-eight, and fifty athletes (18-35 years; black- and red-belt level) were included in the final analysis for aerobic, anaerobic, and agility assessments, respectively. Maximum oxygen uptake (VO2max, using a graded exercise test on a treadmill), anaerobic power (using the 30-s Wingate anaerobic test, WAnT), and agility performance (using the agility T-Test) were measured via non-specific laboratory and field tests across a two-week period. The taekwondo-specific aerobic-anaerobic-agility (TAAA) test comprised six 20-s intervals of shuttle sprints over a 4-m distance, and the execution of roundhouse kicks alternating the legs at the end of each distance, with 10-s rest intervals between the sets. The multiple linear regression revealed that the difference between heart rate (HR) after and 1 minute after the TAAA test (p < 0.001), and body mass index (BMI; p = 0.006) were significant to estimate VO2max. Likewise, there was a very large (R = 0.79) and large (R = 0.55) correlation between the average and maximum number of kicks performed in the TAAA test and the WAnT mean and peak power, respectively (p < 0.001). Moreover, a linear relationship was found between the T-Test and agility performance acquired in the TAAA test (R = 0.74; p < 0.001). The TAAA test can be considered a valid simple tool for monitoring VO2max, anaerobic fitness, and agility in male taekwondo athletes.